Effect of short pulse laser patterning on adhesion of resin-matrix cements to zirconia - Sahoo, Narayan (2021)
Yttria-stabilized tetragonal zirconia polycrytsal (Y-TZP) owing to its excellent mechanical properties, high degree of biocompatibility and attractive aesthetic properties have emerged as a popular dental biomaterial[1]–[4] Out of all zirconia system 3mol% yttria stabilized zirconia (3Y-TZP) have been used for monolithic crowns, inlays, onlays, dental posts and several other types of indirect restorations[5]. However zirconia is chemically inert and demands surface modification for strong bonding to its underlying substrate[6]–[11] It is highly crystalline in structure and is not readily etched with mineral acids. Several surface modification strategies have been employed so far for increasing adhesion of zirconia to its underlying substrate[12]– [14]. However there is so far no gold standard have been established for adhesion to zirconia. It also have weak adhesion when resin-matrix cements are used for bonding restorations. Air particle abrasion using Alumina (Al2O3) and Silica(SiO2) coated particles are popularly used for surface roughening and increasing bond strength. However they produces surface flaws and can be detrimental to longevity of restorations[14]–[16] Photo machining by the application of LASER (Light Amplification by Stimulated Emission of Radiation) offers an alternative due to its simplicity, flexibility, precision, and reproducibility and relatively low cost for increasing surface roughness and improving adhesion to zirconia[17]–[20] Therefore this study employed Nd:YAG laser for surface structuring and compared with conventional surface modification methods such as alumina blasting and compared the surface qualitatively as well as the resulting bond strengths are also compared